2017
DOI: 10.1021/acsami.6b16228
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable Potentiometric pH Sensor Fabricated via Laser Carbonization and Machining of Carbon−Polyaniline Composite

Abstract: The development of stretchable sensors has recently attracted considerable attention. These sensors have been used in wearable and robotics applications, such as personalized health-monitoring, motion detection, and human-machine interfaces. Herein, we report on a highly stretchable electrochemical pH sensor for wearable point-of-care applications that consists of a pH-sensitive working electrode and a liquid-junction-free reference electrode, in which the stretchable conductive interconnections are fabricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
118
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 46 publications
3
118
0
1
Order By: Relevance
“…[1][2][3][4] Organic semiconductors, especially those based on conjugated polymers, are promising towards these ends and have been explored extensively. [5][6][7][8] While these materials offer extraordinary properties, production scale manufacturing of devices based on many of these materials remains a chemistry and engineering challenge due to a variety of factors. One issue relates to making large, even, and defect free films on transparent electrodes that are sufficient for device applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Organic semiconductors, especially those based on conjugated polymers, are promising towards these ends and have been explored extensively. [5][6][7][8] While these materials offer extraordinary properties, production scale manufacturing of devices based on many of these materials remains a chemistry and engineering challenge due to a variety of factors. One issue relates to making large, even, and defect free films on transparent electrodes that are sufficient for device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the straightforward transduction principle and simple readout configuration, potentiometric pH sensors have been the dominant instrument used for pH sensing, including stretchable pH sensors. 112,121,188 The spectrometric pH sensor is an alternative sensing technique. Unlike electrochemical pH sensing, the spectrometric technique indirectly acquires the pH of a solution by measuring the concentration of the acidic and basic forms of the pH indicators.…”
Section: Ph Sensorsmentioning
confidence: 99%
“…Non-stretchable ISE materials were optimized through geometry engineering into meander/serpentine patterns and island-bridge configurations to produce stretchable pH sensors. 121,188 In 2014, Chung et al reported an island-bridge strategy enabled stretchable pH sensor array. 191 In 2015, Hwang et al reported the production of stretchable Si NM-and Si NR-based transient electronics with device islands connected by serpentine or out-out-plane interconnects that allow the system to accommodate large deformations without fracture.…”
Section: Ph Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] With a soft polymer, to the traditionally adopted direct heating method for polymer carbonization lie on its patternability in ambient environment with more flexibility, versatility, and highly controlled fashion. DLWc has been successfully applied to fabricate carbon patterns targeted for a variety of interesting applications, e.g., supercapacitors, [37][38][39][40][41] flexible electrodes, [42] heating elements, [43] various sensors for detecting/measuring sound and vibration, [39] strain or stress, [44][45][46] humidity, [46] pH value, [47] and biomolecules. [48] Given the success of DLWc, its use for fabricating dense, homogenous, and ultrathin carbon films is still a challenge.…”
Section: Introductionmentioning
confidence: 99%